2012
DOI: 10.1002/aenm.201200249
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube‐Silicon Solar Cells

Abstract: Due to the high cost of silicon photovoltaics there is currently great interest in finding alternative semiconductor materials for light harvesting devices. Single‐walled carbon nanotubes are an allotrope of carbon with unique electrical and optical properties and are promising as future photovoltaic materials. It is thus important to investigate the methods of exploiting their properties in photovoltaic devices. In addition to already extensive research using carbon nanotubes in organic photovoltaics and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
159
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 129 publications
0
159
0
1
Order By: Relevance
“…Carbon nanotubes are one of the allotropes of carbon and due to their excellent electrical and optical properties [4,5], they have been applied in new generation solar cells [6,7], such as those using CNT-Si heterojunctions [8]. The structure of a CNT-Si heterojunction solar cell is similar to that of an n-type monocrystalline silicon solar cell but with replacement of the p-type emitter layer and front contact metallization by a CNT film, which serves both purposes.…”
Section: Introductionmentioning
confidence: 96%
“…Carbon nanotubes are one of the allotropes of carbon and due to their excellent electrical and optical properties [4,5], they have been applied in new generation solar cells [6,7], such as those using CNT-Si heterojunctions [8]. The structure of a CNT-Si heterojunction solar cell is similar to that of an n-type monocrystalline silicon solar cell but with replacement of the p-type emitter layer and front contact metallization by a CNT film, which serves both purposes.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, SWCNTs/n-Si PV devices have evolved into their own field of research at the intersection of well-established silicon-based technology and cutting-edge nanomaterial science. These devices typically rely on nanoheterojunctions of n-type silicon and p-type SWCNTs films [6][7][8][9][10][11]. It has been reported that the transparency and electrical conductivity of the SWCNTs films play a direct role in the performance of such PV devices [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Outstanding mechanical [1], electrical [2], and thermal properties [3] of CNTs makes them a promising candidate for a wide variety of applications, such as biomedical science [4], field emission [5], super-capacitors [6], molecular sensors [7] reinforced composites [8], therapeutics [9], antitumor therapeutics [10], gene or drug delivery [11], transistors [12], solar cells [13], catalyst supports [14], hydrogen storage [15], gas separation [16], lithium batteries [17] and so on [18,19]. However, their insolubility in both water and organic solvents hinders the path toward the practical applications of this unique class of materials.…”
Section: Introductionmentioning
confidence: 99%